The hidden feast : a folktale from the American South - Hamilton, Martha (August House LittleFolk, 2006)
The barnyard animals have a good time at their neighbors' party until dinner is served, when the feast appears to be disappointing and Rooster rudely storms off before discovering a hidden treat.